Intelligent reconstruction for spatially irregular seismic data by combining compressed sensing with deep learning - Gong, Xinyue; Chen, Shengchang; Jin, Chengmei (Frontiers in Earth Science, 2023)
Data reconstruction is the most essential step in seismic data processing. Although the compressed sensing (CS) theory breaks through the Nyquist sampling theorem, we previously proved that the CSbased reconstruction of spatially irregular seismic data could not fully meet the theoretical requirements, resulting in low reconstruction accuracy. Although deep learning (DL) has great potential in mining features from data and accelerating the process, it faces challenges in earth science such as limited labels and poor generalizability. To improve the generalizability of deep neural network (DNN) in reconstructing seismic data in the actual situation of limited labeling, this paper proposes a method called CSDNN that combines model-driven CS and data-driven DNN to reconstruct the spatially irregular seismic data. By physically constraining neural networks, this method increases the generalizability of the network and improves the insufficient reconstruction caused by the inability to sample randomly in the whole data definition domain. Experiments on the synthetic and field seismic data show that the CSDNN reconstruction method achieves better performance compared with the conventional CS method and DNN method, including those with low sampling rates, which verifies the feasibility, effectiveness and generalizability of this approach. This is a provisional file, not the final typeset article acquisition environment and economic factors constrains in exploration, the obtained spatially irregular and incomplete seismic data usually cannot satisfy the Nyquist-Shannon sampling theorem. Such missing trace data seriously affects the subsequent seismic data processing, which in turn impairs the reliability of the final interpretation. Thus, effective reconstruction is meaningful for seismic data processing to accurately depict complex geological structures and provide more effective instructio ns and assistance for petroleum exploration.Currently, the major ap proaches used to reconstruct spatially irregularly distributed seismic data include model-driven methods based on the knowledge of mathematical equations or time-space variation characteristics, and data-driven methods based on deep learning (DL) from big data.Model-driven methods mainly encompass predictive filtering methods (Spitz, 1991), wave equation